Toxin-Antitoxin Gene Pairs Found in Tn3 Family Transposons Appear To Be an Integral Part of the Transposition Module - Lima-Mendez, Gipsi; Alvarenga, Danillo Oliveira [UNESP]; Ross, Karen; Hallet, Bernard; Van Melderen, Laurence; Varani, Alessandro [UNESP]; Chandler, Michael (Amer Soc Microbiology, 2020)
Much of the diversity of prokaryotic genomes is contributed by the tightly controlled recombination activity of transposons (Tns). The Tn3 family is arguably one of the most widespread transposon families. Members carry a large range of passenger genes incorporated into their structures. Family members undergo replicative transposition using a DDE transposase to generate a cointegrate structure which is then resolved by site-specific recombination between specific DNA sequences (res) on each of the two Tn copies in the cointegrate. These sites also carry promoters controlling expression of the recombinase and transposase. We report here that a number of Tn3 members encode a type II toxin-antitoxin (TA) system, typically composed of a stable toxin and a labile antitoxin that binds the toxin and inhibits its lethal activity. This system serves to improve plasmid maintenance in a bacterial population and, until recently, was believed to be associated with bacterial persistence. At least six different TA gene pairs are associated with various Tn3 members. Our data suggest that several independent acquisition events have occurred. In contrast to most Tn3 family passenger genes, which are generally located away from the transposition module, the TA gene pairs abut the res site upstream of the resolvase genes. Although their role when part of Tn3 family transposons is unclear, this finding suggests a potential role for the embedded TA in stabilizing the associated transposon with the possibility that TA expression is coupled to expression of transposase and resolvase during the transposition process itself. IMPORTANCE Transposable elements (TEs) are important in genetic diversification due to their recombination properties and their ability to promote horizontal gene transfer. Over the last decades, much effort has been made to understand TE transposition mechanisms and their impact on prokaryotic genomes. For example, the Tn3 family is ubiquitous in bacteria, molding their host genomes by the paste-and-copy mechanism. In addition to the transposition module, Tn3 members often carry additional passenger genes (e.g., conferring antibiotic or heavy metal resistance and virulence), and three were previously known to carry a toxin-antitoxin (TA) system often associated with plasmid maintenance; however, the role of TA systems within the Tn3 family is unknown. The genetic context of TA systems in Tn3 members suggests that they may play a regulatory role in ensuring stable invasion of these Tns during transposition.
Keywords: antitoxin; Tn3 family; toxin; transposition